Carvacrol and Cinnamaldehyde as Next Generation Antimicrobial Agents against Foodborne Pathogens: Antibacterial Efficacy and Synergistic Interaction with Nisin (Bangladesh Journal of Microbiology, 2023)
Foodborne infections cause substantial issues all around the world, hence food safety is a major public health concern. The goal of this research is to provide information to the scientific community on the possible application of two plant essential oil molecules, Carvacrol (CAR) and Cinnamaldehyde (CN), as next-generation antimicrobials in the fight against foodborne pathogens. CAR and CN demonstrated outstanding dose-dependent antibacterial efficacy against 10 foodborne pathogens. Both Gram-positive and Gram-negative bacteria were suitably inhibited by the drugs. Antimicrobial activity of 10% v/v CAR and CN was much higher than that of the conventional antibiotic azithromycin (15g/disc). The study discovered that CAR and CN have very low MIC values (0.08% to 0.31% v/v), indicating that the compounds are efficacious even at very low concentrations. Even at 0.16% concentration, combining CAR and CN with Nisin (a widely available natural preservative) exhibited substantial synergism, with inhibition zones ranging from 8.5- 12.38 mm, decreasing the dose required to produce sufficient antimicrobial action. The findings imply that CAR and CN combined with nisin can be used as a natural antibacterial agent to limit the growth of foodborne pathogens and as a natural food preservative.Bangladesh J Microbiol, Volume 39, Number 1, June 2022, pp 7-14